Fevipiprant (QAW039) does not affect the pharmacokinetics of zidovudine, its glucuronide, and penicillin G via inhibition of UGT2B7 and/or OAT3. (February 2022) - Kulkarni, Swarupa; Poller, Birk; Drollmann, Anton; Shah, Bharti; Gray, Cathy; Greco, Erin; Rahmanzadeh, Gholamreza; Hanna, Imad; Weiss, H Markus
Highlights: AZT and its glucuronide can serve as combined probes for UGT2B7 and OAT3. Fevipiprant does not inhibit UGT2B7 and OAT3 in vivo . Fevipiprant, AZT, and penicillin G are well tolerated, alone or in combination.